Upregulation of LIMK1 Is Correlated With Poor Prognosis and Immune Infiltrates in Lung Adenocarcinoma - Lu, Guojun; Zhou, Ying; Zhang, Chenxi; Zhang, Yu (Frontiers in Genetics, 2021)
Background: Protein-coding gene LIM Domain Kinase 1 (LIMK1) was previously reported in various diseases. However, the mRNA expression and prognostic values of LIMK1 in lung adenocarcinoma are still not understood. Therefore, we evaluated the mRNA expression and prognostic role of LIMK1 in lung adenocarcinoma based on data from the Cancer Genome Atlas (TCGA). Methods: Transcriptional expression profiles of LIMK1 between lung adenocarcinoma tissues and normal tissues were compared. The LIMK1 protein expression was assessed by the Human Protein Atlas. Receiver operating characteristic (ROC) curve was used to differentiate lung adenocarcinoma from adjacent normal tissues. Kaplan-Meier method was conducted to show survival characteristics. Protein-protein interaction (PPI) networks were constructed by the STRING. Functional enrichment analyses were performed using the “ClusterProfiler” package. The relationship between LIMK1 mRNA expression and immune infiltrates was determined by tumor immune estimation resource (TIMER) and tumor-immune system interaction database (TISIDB). Results: The expression of LIMK1 in lung adenocarcinoma tissues was significantly upregulated than those in adjacent normal tissues. Increased LIMK1 mRNA expression was associated with lymph node metastases and high TNM stage. The ROC curve analysis showed that with a cutoff level of 4.908, the accuracy, sensitivity, and specificity for LIMK1 differentiate lung adenocarcinoma from adjacent controls were 69.5%, 93.2%, and 71.9%, respectively. Kaplan-Meier survival analysis showed lung adenocarcinoma patients with high-LIMK1 had a worse prognosis than those with low-LIMK1 (43.1 months vs. 55.1 months, P = 0.028). Correlation analysis indicated LIMK1 mRNA expression had significant correlations with tumor purity and immune infiltrates. Conclusion: Upregulated LIMK1 is significantly correlated with poor survival and immune infiltrates in lung adenocarcinoma. Our study suggests that LIMK1 can be used as a poor prognostic biomarker and potential immune therapy target in lung adenocarcinoma.